2019
DOI: 10.1016/j.jhazmat.2019.120778
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial immune and stress response, cytoskeleton and signal transduction effects of graphene and triphenyl phosphate (TPP) in mussel Mytilus galloprovincialis

Abstract: Owing to its unique surface properties, graphene can absorb environmental pollutants, thereby affecting their environmental behavior. Triphenyl phosphate (TPP) is a highly produced flame retardant. However, the toxicities of graphene and its combinations with contaminants remain largely unexplored. In this work, we investigated the toxicological effects of graphene and TPP to mussel Mytilus galloprovincialis. Results indicated that graphene could damage the digestive gland tissues, but no significant changes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 52 publications
0
4
1
1
Order By: Relevance
“…Developmental neurotoxicity, alteration of neurotransmitters, and gene and protein expression in the central nervous system have been observed in zebrafish larvae (Shi et al 2018 ). In the present study, no effect of TPHP exposure was observed on CAT and GR activities, despite oxidative stress has previously been reported after exposure to other organophosphates in vivo and in vitro, in fish (e.g., the zebrafish, Du et al 2019 ) and marine invertebrates (e.g., the mussel, Mytilus galloprovincialis , Meng et al 2019 ). GST activity remained unchanged at low TPHP concentrations, but a decreasing trend was observed at higher concentrations, which resulted in a reduction of the detoxification efficacy, as shown by the decreasing values of TPHP-exposed larvae along the PC2 axis at the highest TPHP concentrations.…”
Section: Discussioncontrasting
confidence: 55%
“…Developmental neurotoxicity, alteration of neurotransmitters, and gene and protein expression in the central nervous system have been observed in zebrafish larvae (Shi et al 2018 ). In the present study, no effect of TPHP exposure was observed on CAT and GR activities, despite oxidative stress has previously been reported after exposure to other organophosphates in vivo and in vitro, in fish (e.g., the zebrafish, Du et al 2019 ) and marine invertebrates (e.g., the mussel, Mytilus galloprovincialis , Meng et al 2019 ). GST activity remained unchanged at low TPHP concentrations, but a decreasing trend was observed at higher concentrations, which resulted in a reduction of the detoxification efficacy, as shown by the decreasing values of TPHP-exposed larvae along the PC2 axis at the highest TPHP concentrations.…”
Section: Discussioncontrasting
confidence: 55%
“…The proteins that form the mussel byssus are produced in three compartments: the phenol gland (fp-2, fp-3, fp-4, fp-5, fp-6), the core gland (preCol-D, preCol-NG, preCol-P, ptmp-1, tmp-1), and the cuticle gland (fp-1, fp-3) . Among these proteins, fp-2, fp-3A, fp-5, preCol-D, and preCol-NG, with known sequences in Mytilus galloprovincialis , were selected as the targets of qRT-PCR, and β-actin was used as an internal control. The qRT-PCR results showed that the mRNA level of mgfp-5 was upregulated 5.8-fold on the stiff surface compared to the soft surface, similar to the RNA-Seq results, which showed a 5.4-fold difference. In addition, mgfp-3A, preCol-D, and preCol-NG did not show any expression difference, similar to the RNA-Seq results (Figure b,c).…”
Section: Resultsmentioning
confidence: 99%
“…因此, 鳃是与周围环境接触 的第一个部位, 其次是消化腺组织 [41,42] . 紫贻贝呼吸和滤食过程中对鳃组织造成物理损伤, 进 入消化道后可对消化道组织造成损伤 [43] . Ma等人 [ [43] .…”
Section: 氧化应激unclassified